Incidencia del sistema de control interno basado en riesgo empresarial en la gestión financiera de Clínica Cristo Redentor, año 2021 - Alfaro Lavado, Esteban David (2023)
The present investigation consisted of determining how the Internal Control System based on business risk affects the financial management of Clínica Cristo Redentor, Year 2021. The study had a quantitative approach, it was based on the non-experimental design, the correlational design y, cross-section; descriptive and explanatory methods were used; non probabilistic sampling was used, considering the criteria and judgment of the researcher; the technique used is the survey and the instrument used is the questionnaire, which was applied to 8 professionals of the institution; The data collected was processed through the application software MS Excel and, to determine the reliability of the variables, the statistical software SPSS version 25 was used. According to the investigation carried out, it was concluded that the Internal Control System based on business risk had an impact positively in the financial management of Clínica Cristo Redentor, Year 2021; having a degree of significant correlation of 0.994, with a Very Strong Positive relationship, at a significance level of 5%.